2022
DOI: 10.1002/psc.3466
|View full text |Cite
|
Sign up to set email alerts
|

Artificial peptides to induce membrane denaturation and disruption and modulate membrane composition and fusion

Abstract: Membranes consisting of phospholipid bilayers are an essential constituent of eukaryotic cells and their compartments. The alteration of their composition, structure, and morphology plays an important role in modulating physiological processes, such as transport of molecules, cell migration, or signaling, but it can also lead to lethal effects. The three main classes of membrane‐active peptides that are responsible for inducing such alterations are cell‐penetrating peptides (CPPs), antimicrobial peptides (AMPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 265 publications
(475 reference statements)
0
5
0
Order By: Relevance
“…Greater aggregation may lead to decreased antimicrobial activity since interpeptide interactions can prevent attachment to the cell membrane and render the peptide inactive . However, for some AMPs, aggregation is crucial for membrane permeabilization, disruption, and translocation . MD simulations of melittin in a zwitterionic bilayer by Sengupta et al showed that pore formation did not take place unless a cluster of at least three peptides was present .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Greater aggregation may lead to decreased antimicrobial activity since interpeptide interactions can prevent attachment to the cell membrane and render the peptide inactive . However, for some AMPs, aggregation is crucial for membrane permeabilization, disruption, and translocation . MD simulations of melittin in a zwitterionic bilayer by Sengupta et al showed that pore formation did not take place unless a cluster of at least three peptides was present .…”
Section: Resultsmentioning
confidence: 99%
“… 31 However, for some AMPs, aggregation is crucial for membrane permeabilization, disruption, and translocation. 32 MD simulations of melittin in a zwitterionic bilayer by Sengupta et al showed that pore formation did not take place unless a cluster of at least three peptides was present. 33 Peptide activity is potentially enhanced due to a high localized concentration of peptide on the membrane surface prior to subsequent pore formation.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of action involves either disruption of the stability of bacterial membranes or the important internal cell units of bacteria. 19,20 The membrane lytic action is one of the main advantages of AMPs, which has long been believed that is unaffected by the mechanism of action underlying resistance to antibiotics. 21 Despite the fact that AMPs have many benets, there are several obstacles to their protable commercial and therapeutic expansion as medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial peptides (AMPs) have emerged as a promising class of molecules that can be used to address this problem. , These peptides have a broad spectrum of activity against bacteria, fungi, and viruses and are less likely to develop resistance compared to conventional antibiotics. AMPs are produced by various organisms, including plants, animals, and microorganisms, and they play a vital role in the innate immune system’s defense against pathogens. These peptides are typically small and cationic, allowing them to interact with microorganisms’ negatively charged cell membranes, leading to membrane disruption and cell death. , Over the past few decades, there have been substantial progress in the field of AMPs, with an increasing number of these peptides being discovered and characterized. These developments have revolutionized the medicinal field, providing new hope in the fight against drug-resistant infections. The discovery of AMPs has led to the development of various peptide-based drugs with significant potential in the pharmaceutical industry .…”
Section: Introductionmentioning
confidence: 99%
“… 11 13 These peptides are typically small and cationic, allowing them to interact with microorganisms’ negatively charged cell membranes, leading to membrane disruption and cell death. 14 , 15 Over the past few decades, there have been substantial progress in the field of AMPs, with an increasing number of these peptides being discovered and characterized. 16 19 These developments have revolutionized the medicinal field, providing new hope in the fight against drug-resistant infections.…”
Section: Introductionmentioning
confidence: 99%